Analisis Tipe Kesalahan Siswa dalam Menyelesaikan Soal Matematika Berdasarkan Taksonomi Anderson - Purnamayanthi, Komang Tri; Suparta, I Nengah; Suweken, Gde (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
This study analyzed student errors in answering questions with levels C1-C6 based on Anderson's taxonomy on the topic of a three-variable system of linear equations. The research was conducted with a descriptive qualitative approach in which the data were collected through test and interviews by taking 30 tenth grade students at Santo Joseph Senior High School Denpasar as the subjects. Students were given 6 math problems, which were then analyzed for errors and followed by interviewing students to find the cause of their errors. The results of the percentage of student errors based on the type of error were incomplete answers at 46.8%, technical errors at 25.5%, errors in understanding the previous material at 16.6%, language misinterpretation at 5.5%, data misuse at 4.5%, and unverified solutions at 1.1%. From the results of the interviews, it was found that the causes of the errors were poor time management, low motivation to try to solve problems, not understanding the problem, not doing re-examination, being careless, errors in assuming that occurred due to students' spontaneous thinking without examining the meaning of the problem, students did not understand the concept that was related to procedures in solving problems, and less attention to the results of the answers made. The results indicated that there were errors at each level, especially at higher levels which have an impact on the need to increase practice questions at levels C4, C5, and C6 so that the students' understanding is better and the motivation to solve the problems given is increased.